2019
DOI: 10.1371/journal.pone.0211133
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality in patients with suspected sepsis at the Emergency Department; A retrospective cohort study comparing qSOFA, SIRS and National Early Warning Score

Abstract: ObjectiveIn hospitalized patients, the risk of sepsis-related mortality can be assessed using the quick Sepsis-related Organ Failure Assessment (qSOFA). Currently, different tools that predict deterioration such as the National Early Warning Score (NEWS) have been introduced in clinical practice in Emergency Departments (ED) worldwide. It remains ambiguous which screening tool for mortality at the ED is best. The objective of this study was to evaluate the predictive performance for mortality of two sepsis-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
107
2
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 28 publications
12
107
2
14
Order By: Relevance
“…11 Our findings are consistent with the broader literature demonstrating superior performance of NEWS over qSOFA and SIRS in predicting mortality. 13,23,24,25 Although other studies have reported SOFA as being superior to NEWS in predicting mortality, 14,26 this was not replicated in our data. Indeed, SOFA had poorer performance characteristics in our cohort than reported in other retrospective studies.…”
Section: Discussioncontrasting
confidence: 82%
“…11 Our findings are consistent with the broader literature demonstrating superior performance of NEWS over qSOFA and SIRS in predicting mortality. 13,23,24,25 Although other studies have reported SOFA as being superior to NEWS in predicting mortality, 14,26 this was not replicated in our data. Indeed, SOFA had poorer performance characteristics in our cohort than reported in other retrospective studies.…”
Section: Discussioncontrasting
confidence: 82%
“…NEWS is a widely used to identify clinically-deteriorating patients, and it has been proven to have better accuracy both in wards and in the ED. [15][16][17][18] Similar to previous studies, 15,16 we found that NEWS without baseline risk model could outperform SIRS and qSOFA in AUROC. It also showed higher NB than qSOFA and SIRS over a narrow range of threshold probability.…”
Section: Discussionsupporting
confidence: 82%
“…This could be evidenced by the much lower validation AUROCs in our study compared to other studies from higher-income countries, which shows poor transportability of their ndings to our setting. [15][16][17][18][19] Moreover, the length of hospital stay range was as much as 310 days and the median time to mortality in our cohort was 27 days (data not shown), indicating prolonged hospital length of stay that may have been due to the lack of hospice service provision in Thailand. Therefore, our mortality within 7 days of admission outcome may be a more valid outcome de nition for sepsis-related mortality in our setting and other similar settings.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the intensive care units, as in the ED or in lower intensity wards, early diagnosis and rapid treatment initiation are even more crucial for halting progression of disease and poor patient prognosis [1,2,33]. The qSOFA and NEWS (National Early Warning Score) scores have been proposed and frequently implemented as a tool to frequently screen patients with infection at risk of organ dysfunction and death [34][35][36][37], as widespread and frequent monitoring of biomarkers as PCT may be impractical or too expensive in these settings. Haydar et al (2017) reported the qSOFA score was efficacious for the identification of patients with sepsis at increased risk of mortality, while performing poorly as a screening tool for early identification of sepsis in the emergency department [33].…”
Section: Discussionmentioning
confidence: 99%